Internal investigations and the principle nemo tenetur se ipsum accusare – The Austrian perspective - Soyer , Richard (European Integration Studies, 2023)
There is no general one but there are limited specific obligations in Austria to carry out Internal Investigations. The Austrian Constitutional Court clarified in a ruling 2016 inter alia that the principles of Article 6 of the European Convention on Human Rights concerning procedural guarantees apply to corporations as well. Yet, it has been accepted also before that the nemo tenetur principle also applies to legal persons. However, disputed questions still exist.